Relationship quality among dating adolescents: Development and validation of the Relationship Quality Inventory for Adolescents - Fortin, Andréanne; Fortin, Laurie; Paradis, Alison; Hébert, Martine (Frontiers in Psychology, 2022)
Relationship quality has implications for individuals’ and couples’ well-being, such as higher couple functioning and perceived quality of life. In adolescence, low relationship quality has been associated with poor mental health and relational outcomes. However, given the lack of instruments to assess satisfaction in dating relationships, most studies have relied on measures of marital satisfaction. The current study aimed to address this gap by elaborating and validating the Relationship Quality Inventory for Adolescents (RQI-A). Exploratory and confirmatory factor analyses were conducted among two samples of dating adolescents (n1=310; n2=335). The two-factor structure (Connectedness and Commitment) was cross-validated, and dimensions showed high internal consistency coefficients (ω=.86-.89). Results also provide evidence of convergent validity of the scale with related measures. The RQI-A may help study predictors and correlates of dating relationship quality.